1979
DOI: 10.1016/0022-3115(79)90339-8
|View full text |Cite
|
Sign up to set email alerts
|

A helium-induced shift in the temperature dependence of swelling

Abstract: In an annealed austeniiic alloy undergoing bombardment with k MeV Ni ions to doses between I and 70 dpa at 840, 900, 950, 1025 and 1100 K, the introduction of simultaneously-implanted helium at a rate of 20 appm He/dpa moves the swelling versus temperature curve up the temperature scale by ItO to 70 K. Co-implantation of hydrogen (deuterium) at a rate of 50 appm D/dpa simultaneously with the helium causes little or no additional syste ,atic effects. The major change in microstructure caused by the gases is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 6 publications
3
11
0
Order By: Relevance
“…12 shows the expected bell-shaped swelling curve as a function of temperature. This agrees with expected results from both void swelling theory [10] and the literature [8,9]. Void diameter and number density also follow the same behavior with temperature.…”
Section: Effect Of Helium On Swellingsupporting
confidence: 91%
See 2 more Smart Citations
“…12 shows the expected bell-shaped swelling curve as a function of temperature. This agrees with expected results from both void swelling theory [10] and the literature [8,9]. Void diameter and number density also follow the same behavior with temperature.…”
Section: Effect Of Helium On Swellingsupporting
confidence: 91%
“…However, these results differ in that the swelling peak is narrower than that seen in the literature. [8,9] The full width at tenth maximum (FWTM) for alloy HT9 in Smidt's experiment was approximately 100°C. Toloczko [24] recently reported the temperature dependence on swelling of MA957, in which the FWHM was $90°C.…”
Section: Effect Of Helium On Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to tungsten vacancies having no thermal mobility at the low temperature resulting in the bubbles growing through interstitial emission, whereas at the higher irradiation temperatures, He bubble growth resulted from the capture of the thermally mobile, radiation-induced vacancies. Similar effects are also observed when irradiating steels such as HT-9 and EM-12 with He ions [30,31].…”
Section: Fig 4 A) Atom Map Showing Onlysupporting
confidence: 54%
“…This phenomenon was discovered by Evans [8]. Partially ordered void super-lattices have been reported for irradiated pure materials, for example, Mo [8], Al [9], Nb [10], Ni [11], and alloys: Ni-Al [12], Cu-10%Ni [13], Nb-Zr [14], Mo-0.5Ti [15], stainless steel [16,17] irradiated to damage levels of 10−80 dpa (displacements per atom) [18]. It was found that typical void size is 2−7 nm in pure materials with void super-lattice parameter 20−30 nm, whereas for steels, the void size is around 30−100 nm, depending on irradiation conditions (dose rate and temperature).…”
Section: Introductionmentioning
confidence: 99%